A NEW CESTODE COTUGNIA SINGHI N.SP. (EUCESTODA : DAVAINDIAE, DIAMARE, 1893) FROM COLUMBA LIVIA AT AURANGABAD, INDIA - PAWAR, S.B.; SHINDE, G.B.; GARAD, V.B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The present form deals with description of genus Cotugnia Diamare, 1893, with type species C digonopora (Pasquale, 1890) in Africa, in having testes number 65-70 comes closer to C joyeuxi Baer, 1925; C fleari Meggitt, 1927; C. cuneata tenuis Meggitt, 1924 and C rajivi Jadhav et al. (1994). However, it differs from them in size of scolex, size of rostellum, number of rostellar hooks, number of testes and length of cirrus pouch.